Factors that Influence the Resilience of Muhammadiyah Member's Families during the COVID-19 Pandemic in Surabaya, Indonesia - Mundakir, Mundakir; Choliq, Idham; Nasrullah, Dede; Syarifurrahman, Islam; Firman, Firman; Fitriani, Vika Ramadhana (Jurnal Keperawatan Soedirman, 2023)
COVID-19 has created uncertainty, and its impacts will undoubtedly be severe, long-lasting, and challenging from socioeconomic and psychological perspectives, particularly for families worldwide. This research identified the resilience level of Muhammadiyah members' families in Surabaya during the COVID-19 pandemic and explained the factors related to their family resilience. This research used a cross-sectional method. The samples were 289 respondents, with the inclusion criteria of either the husband or wife being a Muhammadiyah member in Surabaya. The sampling technique used stratified multistage random sampling. The research location was divided into 5 regions: Central Surabaya, North Surabaya, West Surabaya, South Surabaya, and East Surabaya. Descriptive analysis and Chi-Square statistical test were used. The results of this study indicate that the family resilience of Muhammadiyah members obtained a high score during the pandemic. The factor that influenced family resilience was the location of residence, which obtained a p-value of 0.00, which is less than 0.05. Meanwhile, gender, location of residence, age, occupation, income, and education did not affect the level of family resilience. Further research is needed to develop a family resilience intervention model to improve family resilience.